NKLP27: a teleost NK-lysin peptide that modulates immune response, induces degradation of bacterial DNA, and inhibits bacterial and viral infection. - Min Zhang (Public Library of Science (PLoS), 2014)
NK-lysin is an antimicrobial protein produced by cytotoxic T lymphocytes and natural killer cells. In this study, we examined the biological property of a peptide, NKLP27, derived from tongue sole (Cynoglossus semilaevis) NK-lysin. NKLP27 is composed of 27 amino acids and shares little sequence identity with known NK-lysin peptides. NKLP27 possesses bactericidal activity against both Gram-negative and Gram-positive bacteria including common aquaculture pathogens. The bactericidal activity of NKLP27 was dependent on the C-terminal five residues, deletion of which dramatically reduced the activity of NKLP27. During its interaction with the target bacterial cells, NKLP27 destroyed cell membrane integrity, penetrated into the cytoplasm, and induced degradation of genomic DNA. In vivo study showed that administration of tongue sole with NKLP27 before bacterial and viral infection significantly reduced pathogen dissemination and replication in tissues. Further study revealed that fish administered with NKLP27 exhibited significantly upregulated expression of the immune genes including those that are known to be involved in antibacterial and antiviral defense. These results indicate that NKLP27 is a novel antimicrobial against bacterial and viral pathogens, and that the observed effect of NKLP27 on bacterial DNA and host gene expression adds new insights to the action mechanism of fish antimicrobial peptides.